Republic of Korea : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Korea. (IMF Staff Country Reports; Country Report ;, 2018)
This 2017 Article IV Consultation highlights that the Republic of Korea's near-term outlook is improving. After slowing in the second half of 2016, growth has picked up in 2017, while recent geopolitical tensions have had a limited impact. The rebound was led by a strong expansion in investment, especially in the information technology and construction sectors. Export growth strengthened thanks to improving external conditions and high global demand for semiconductors. Private consumption growth picked up, but remains below economic growth. Recovery has been supported by an accommodative monetary policy, with lending rates and long-term yields close to record lows.